Alkaline-promoted Ni based ordered mesoporous catalysts with enhanced low-temperature catalytic activity toward CO2 methanation. Issue 30 (27th March 2017) - Xu, Leilei; Wang, Fagen; Chen, Mindong; Yang, Haoming; Nie, Dongyang; Qi, Lu; Lian, Xinbo
Abstract : Mg alkaline-promoted Ni ordered mesoporous catalysts possess enhanced catalytic activities and stabilities toward CO2 methanation due to decreasing CO2 activation energy. Abstract : For CO2 methanation reaction, a Mg species is often utilized as the alkaline promotor for Ni based catalysts to enhance the low-temperature catalytic activity. Herein, based on a pioneer ordered mesoporous NiO–Al2 O3 catalyst, a Mg alkaline promotor had been incorporated into the ordered mesoporous framework via a one-pot evaporation induced self-assembly (EISA) strategy. As a result, the ordered mesoporous NiO–MgO–Al2 O3 composite oxides with Mg/Al molar ratios in a wide range (0–10%) were successfully fabricated and directly utilized as the catalysts for CO2 methanation reaction. These mesoporous catalysts were carefully characterized by X-ray diffraction, N2 adsorption–desorption, transmission electron microscopy, selected area electron diffraction, energy dispersive spectrometer, X-ray photoelectron spectroscopy, H2 temperature-programmed reduction, and CO2 temperature-programmed desorption measurements. It was found that the ordered mesoporous materials with large specific surface areas (180.8–232.8 m 2 g −1 ), big pore volumes (0.37–0.43 cm 3 g −1 ), and narrow pore size distributions (around 9.5 nm) could be successfully retained after the calcination at 700 °C. The highly dispersed Ni species were strongly interacted with the mesoporous framework in the form of NiAl2 O4 spinel. The incorporation of the Mg progressively increased the surface basicity of these catalysts, which could intensify the chemisorption and activation of CO2 during the CO2 methanation reaction. Therefore, the low-temperature catalytic activity was significantly enhanced. The "volcano-shape curve" relationship between the Mg/Al molar ratio and catalytic activity had been interestingly observed, suggesting only appropriate surface basicity could obtain the optimum catalytic activity. Besides, there was no evident deactivation over these mesoporous catalysts after 50 h long-term stability tests due to the confinement effect of the mesoporous framework. Therefore, the present ordered mesoporous NiO–MgO–Al2 O3 materials could be considered as a series of potential catalyst candidates for CO2 methanation.